Does botulinum toxin A combined with bracing prevent hip displacement in children with cerebral palsy and "hips at risk"? A randomized, controlled trial - Graham, H.; Boyd, Roslyn; Carlin, J.; Dobson, F.; Lowe, K.; Nattrass, G.; Thomason, P.; Wolfe, R.; Reddihough, D. (2008)
Background: Cerebral palsy is the most common cause of childhood physical disability in developed countries, affecting two children per 1000 live births. Hip displacement affects about one-third of children with cerebral palsy and may result in pain, deformity, and impaired function. The prevention of hip displacement has not been studied in a randomized trial as far as we know. Methods: A randomized, controlled trial was conducted to examine the effect of intramuscular injections of botulinum toxin A combined with use of a variable hip abduction brace on the progression of hip displacement in children with cerebral palsy. The patients in the treatment group received injections of botulinum toxin A to the adductor and hamstring muscles every six months for three years and were prescribed a hip abduction brace to be worn for six hours per day. In the control group, no hip bracing was used nor were injections performed. The primary outcome measure was hip displacement from the acetabulum as determined by serial measurements of the migration percentage. Results: Ninety children with bilateral cerebral palsy and so-called hips at risk (a migration percentage of >10% but <40%) were entered into the study. Fifty-nine patients were boys, and the mean age was three years. Progressive hip displacement, as determined by serial measurements of the migration percentage, was found in both the treatment and control groups. The rate of hip displacement was reduced in the treatment group by 1.4% per year (95% confidence interval, -0.6% to 3.4%; p = 0.16) when weighted for the uncertainty in rates due to the differing numbers of migration percentage measurements per subject. Conclusions: There may be a small treatment benefit for the combined intervention of intramuscular injection of botulinum toxin A and abduction hip bracing in the management of spastic hip displacement in children with cerebral palsy. However, progressive hip displacement continued to occur in the treatment group, and our data do not support recommending this treatment. Level of Evidence: Therapeutic Level I. See Instructions to Authors for a complete description of levels of evidence. Copyright © 2008 by The Journal of Bone and Joint Surgery, Incorporated.